Infrastructure, women's time allocation, and economic development. - Agénor, Pierre-Richard.; Agénor, Madina. (Tufts University. Tisch Library., 2019)
This paper develops a gender-based OLG model of endogenous growth to analyze the impact of infrastructure on women's time allocation between market work, raising children, own health care, and home production, and its implications for education and health outcomes. Women's health status in adulthood, which affects productivity and wages, depends on their health status in childhood. Threshold effects in health and life expectancy, associated with access to infrastructure, may generate multiple development regimes. Whether an increase in government investment in infrastructure succeeds in shifting the economy to a high-growth equilibrium depends crucially on how women reallocate their time and the strength of congestion effects.